The S‐Cycle Performance Matrix: Supporting Comprehensive Sustainability Performance Evaluation of Technical Systems. Issue 1 (2nd May 2017) - Hay, L.; Duffy, A. H. B.; Whitfield, R. I.
ABSTRACT: In this paper, we present the first generic framework for selecting comprehensive material/energetic sustainability performance indicators (SPIs) for technical systems: the S‐Cycle Performance Matrix (S‐CPMatrix). This novel matrix is comprised of 6 generic sustainability goals, 11 SPI archetypes, and 23 corresponding metrics identified from our previously developed model of technical system sustainability (the S‐Cycle), and is intended to support decision makers in meeting three identified criteria for comprehensive SPI sets: (C1) inclusion of indicators measuring performance at all relevant scales; (C2) inclusion of efficiency and effectiveness indicators; and (C3) coverage of all system sustainability goals. We evaluated the matrix by interpreting and classifying 324 indicators currently applied to assess technical system sustainability performance in the literature, with 94.1% found to be fully classifiable with respect to the proposed goals and SPI archetypes following several refinements. The matrix is applicable to different systems, and may be considered to facilitate the selection of a holistic set of SPIs from different sources and evaluation approaches. Thus, it addresses a need for consistent yet flexible guidance on how to comprehensively assess technical system sustainability performance, mirroring generic guidelines on organizational SPI selection widely available through several international initiatives. In addition to industrial evaluation of the S‐CPMatrix, four avenues for future research are proposed: (i) use of the matrix for systems comparison/benchmarking; (ii) further investigation of unsupported metrics; (iii) the nature and measurement of contaminants; and (iv) assessing the comprehensiveness of current SPI sets for technical systems.